Editorial: Recent Progress in Algal Biotechnology. Issue 3 (1st March 2016) - Chang, Jo‐Shu; Posten, Clemens
Abstract : In light of the rapid developments in the algal biotech area, this Special issue entitled "Algal Biotechnology" is presented to cover the current advances and updates in this fast‐growing field and also to highlight some recent innovative developments in this area.